Emotional connectivity in branded entertainment and the gender divide. - Chee, Shona Ee Lin. (2012)
The increasing inundation of the media space with consumer messages necessitates a strong, intangible emotional link with consumers in order for brands to break through the clutter. This study examines the relationship between branded entertainment and emotional connectivity while exploring the effects of gender differences on this relationship.